Buckling of bi-segment spherical shells under hydrostatic external pressure. (November 2017) - Zhang, Meng; Tang, Wenxian; Wang, Fang; Zhang, Jian; Cui, Weicheng; Chen, Yun
Abstract: This paper focuses on bi-segment spherical shells under uniform external pressure. The numerical and experimental results of buckling of bi-segment spherical shells with rib-ring of different sizes were discussed. A total of six laboratory scale models with rib-ring of three different sizes were tested. The bi-segment pressure hull was assembly with two individual spherical shells and the rib-ring using the tungsten inert gas butt welding. Each segment was 150 mm diameter and about 0.8 mm wall thickness. Numerical collapse modes agreed well with those obtained from experiments. The predicted collapsed load is about 92–99% of the experimental one except the shell with no rib-ring. Highlights: Geometric, buckling of six bi-sphere shells with rib-ring of three sizes are tested. The effect of rib-ring on buckling are examined numerically and experimentally. Experimental and numerical results are in good agreement except shells with no ring.